IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI DISTRIK SENTANI KABUPATEN JAYAPURA - Axamina Yacadewa; Muammad Musa'ad (Universitas Cenderawasih, 2021)
The purpose of the study was to determine the implementation of Regional Regulation Number 3 of 2012 concerning Waste Management and what internal and external factors support and hinder the implementation of Regional Regulation Number 3 of 2012 concerning Waste Management in Jayapura Regency. The research method used in this research is descriptive qualitative by describing the implementation of Regional Regulation Number 3 of 2012 concerning Waste Management based on Edward III's theory. There were 8 informants in this study. The analysis of this research, namely data collection, data reduction, data presentation and conclusion drawing. The results of the analysis obtained that the implementation of waste management in Sentani, Jayapura Regency, which has occurred so far, if it is associated with the variables of policy implementation from George C. Edward III, still needs improvement. Communication from DLH Jayapura Regency to related elements (stakeholders) has not been optimal so it needs to be intensified. Specifically by DLH to be able to provide education to the public, such as the socialization of Regional Regulation No. 3 of 2012 concerning Waste Management, and counseling/training on procedures for managing household waste to the community. The existing resources (HR, non-HR, financing) in the DLH Jayapura Regency are currently still inadequate, so that it is a serious concern for policy makers to fulfill them. The disposition or behavior of all stakeholders in their respective roles to be able to involve themselves in the waste management program in Sentani City is highly expected. The DLH Bureaucracy Structure in Jayapura Regency still needs improvement, especially in the aspect of Standard Operating Procedures (SOP), as a guide for each implementor to carry out their duties. Supporting factors and obstacles to the implementation of internal factors include limited waste management infrastructure, limited cleaning personnel in waste management, limited funds/budgets to finance waste management activities, as well as enforcement of regulations that do not work, such as fines/sanctions for people who dispose of waste. carelessly. While external factors include aspects of community participation and the level of community participation in the willingness to pay fees/retribution for waste services as well as people who still throw garbage into containers that are not in place and still throw garbage carelessly into rivers, empty land, ditches and others